POLA PERKEMBANGAN PERMUKIMAN NELAYAN DI DUSUN UJUNG PESISI DESA TUMBU, KARANGASEM - Dody Kastama Yasa, I Komang (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2016)
This is a study of a post natural disaster fishing settlement of Ujung Neighborhood in Karangasem Regency on the eastern coast of Bali Island. This settlement was badly hit by the eruption of Mount Agung in 1963. It was then also eroded by significant storms and resultant erosion abrasions over three years from 1997 up to 1999. The study is designed to comprehend the spatial changes that this fishing settlement has been through which have resulted in the development of a currently existing and unique spatial layout. Data used in this study represent spatial changes taking place from 1950 to 2015 when the field survey was conducted. The whole study was approached using qualitative research methods. Research findings have uncovered two prominent spatial patterns. The first is a linear settlement form stretching along the Ujung coastal line and the second a linear and clustered form of spatial pattern demonstrated by Ujung 's mainland settlement. The linear part is oriented towards Seraya-Karangasem road and the clustered pattern takes place in the western part of the neighborhood where social infrastructures are concentrated. These include the facilities of an elementary school, madrasah (Muslim school), and mosque. The study concludes that the development of a post disaster village has followed a mixed spatial pattern for reasons predominantly generated from natural conditions. Keywords : spatial pattern; post-disaster development; fishing settlement Abstrak Studi ini merupakan suatu kajian pasca bencana pada permukiman nelayan di Dusun Ujung Pesisi, Kabupaten Karangsem. Ruang permukiman nelayan Dusun Ujung Pesisi berkembang sejak bencana meletusnya Gunung Agung tahun 1963 dan abrasi pantai pada tahun 1997 sampai 1999. Paper ini bertujuan untuk mengetahui bagaimana pola perkembangan permukiman nelayan yang terjadi di Dusun Ujung Pesisi dari tahun 1950-2015. Penelitian ini dilaksanakan dengan menggunakan metode kualitatif. Data dalam penelitian ini diperoleh melalui studi literatur, grandtour , observasi, wawancara, dan rekonstruksi. Hasil temuan yang ada dilapangan menunjukkan bahwa terdapat dua pola permukiman nelayan di Dusun Ujung Pesisi. Temuan pertama adalah terbentuknya pola linier di sepanjang garis pantai Ujung dan temuan kedua adalah pola linier dan pola cluster di sepanjang daratan Ujung. Pola linier berorientasi ke jalan raya Seraya-Karangasem dan pola cluster berada di sisi barat permukiman. Ini meliputi fasilitas-fasilitas sekolah dasar, madrasah, dan masjid. Kesimpulan dari studi adalah bahwa karena kondisi alam, pembangunan pasca bencana juga diikuti oleh pembentukan permukiman nelayan dengan kombinasi pola-pola ruang yang sudah ada sebelumnya.
Keywords: pola tata ruang; pembangunan pasca bencana; permukiman nelayan